ANTESEDEN DAN KONSEKUENSI MANAJEMEN HUBUNGAN PELANGGAN DALAM INDUSTRI RUMAH SAKIT - Irsan Fitriyandi (Fakultas Ekonomi - Universitas Setia Budi, 2021)
This study aims to examine the Antecedents and Consequences of Customer Relationship Management in PKU Muhammadiyah Surakarta Hospital Industry.The data collection technique in this research is purposive sampling using a questionnaire directly to 80 respondents distributed to outpatients at the PKU Muhammadiyah Surakarta Hospital and 120 online respondents. Hypothesis testing is done by using SEM. The results of this study indicate the quality of service has no significan effect on patient confidence, quality of service has a significan effect on patient commitment, patient satisfaction has a significant effect on patient trust, patient satisfaction has a significant effect on patient commitment, patient value has a significant effect on patient trust, patient value has a significant effect on commitment, trust has a significant effect on patient loyalty, and commitment has a significant effect on patient loyalty. Keywords: Service Quality, Patient Satisfaction, Patient Value, Trust, Commitment, Patient Loyalty.